Association of Carotid Atherosclerosis With Lipid Components in Asymptomatic Low-Income Chinese: A Population-Based Cross-Sectional Study - Pan, Jing; Liu, Jie; Wang, Hong; Li, Weilan; Du, Xin; Lin, Qiuxing; Zhang, Xinxin; Qi, Dongwang; Tu, Jun; Ning, Xianjia; Yang, Qing; Wang, Jinghua (Frontiers in Neurology, 2020)
Intima-media thickness is a non-invasive arterial marker of early-stage atherosclerosis. Identifying carotid plaque is a superior surrogate endpoint for assessing atherosclerotic lesions. The aim of this study was to investigate the association of carotid intima-media thickness (CIMT) and carotid plaque with lipids among asymptomatic low-income rural residents in China. A total of 3,789 people aged ≥45 years without a history of stroke or cardiovascular disease were recruited to this study. B-mode ultrasonography was performed to measure CIMT and identify carotid plaque to early identification of atherosclerosis. Multivariate analysis was used to assess the association of blood lipid levels with atherosclerosis. The mean CIMT across our cohort was 567µm. A linear regression analysis showed that low-density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) was risk factors for early-stage atherosclerosis; however, high-density lipoprotein cholesterol (HDL-C) and triglycerides (TG) protected against early-stage atherosclerosis after adjusting for potential risk factors (P <0.001). Carotid plaque risk increased by 24% and 62% for each 1 mmol/L increase in TC and LDL-C (P<0.001). These findings suggest that it is vital for reducing the burden of CVD to manage and control the dyslipidemia standardized in China, especially among rural residents.